DISEMINASI DAN ALIH TEKNOLOGI KOMPOR SEKAM PADI SISTEM KONTINYU BAGI KELUARGA PRASEJAHTERA - Dwinanto, Matheus M.; Koehuan, Verdy A.; Goetha, Selfiana; Sundari, Woro (Universitas Mataram, 2025)
Rice husks are an agricultural waste product with significant potential as an environmentally friendly alternative energy source through their use as fuel for rice husk stoves. This community service activity aims to be the first step toward achieving energy independence for cooking in Niskolen Hamlet, Tuapanaf Village. The implementation method involves disseminating and transferring rice husk stove technology to pre-prosperous families, ensuring that this appropriate technology will be increasingly sought after and utilized by residents in every hamlet within Tuapanaf Village. The outcome of this community service activity is that the implementation of rice husk stoves will provide economic and social benefits. Rice husks are a cheap and environmentally friendly alternative energy source, utilizing abundant agricultural waste and reducing dependence on kerosene, the availability of which fluctuates. The use of rice husks not only reduces smoke but also shortens cooking time compared to firewood. The time saved from gathering firewood can be used by women for other productive activities or for personal development.